ICO AND STO AS MODERN TOOLS FOR CROWDFUNDING STARTUPS - A. V. Kozhanova (Вестник университета, 2020)
Today financial innovations seem ubiquitous. A new way of attracting capital by startups based on the blockchain such as ICO (initial coin offering) is similar to crowdfunding, selling produced tokens to the pool of investors. With the assistance of this source, startups collected 22 billion dollars in 2018, but in 2019 the market began to fall, so many researchers noted the danger of the ICO bubble. The low survival rate of ICO-projects led to the development of STO (security token offering) market, which guarantees the investor’s secured rights. It has been examined in the article how the new financing instruments can replace traditional ones and how they are adapted to existing legislation. For this purpose, the development of market for these instruments in comparison with traditional ones has been analyzed. The legislation in this area has been studied.